DESAIN PERANGKAT PEMBELAJARAN FISIKA BERORIENTASI STRATEGI KONFLIK KOGNITIF PADA KONSEP KALOR DI KELAS X SMA/MA - Pareni Yonata; Amali Putra; Hufri Hufri (PILLAR OF PHYSICS EDUCATION, 2016)
The background of this research is not to optimize the learning process of learners to construct or establish his own knowledge, this is due to the limited learning device that can help students learn optimally. This study aims to produce a learning device oriented cognitive conflict strategy viable in terms of validity and practicalities.This type of research is the Research and Development (R & D) model of ADDIE (Analyze, Design, Develop, Implement, and Evaluate) which is reduced to develop. Validity and practicalities of involving the six teachers, two teachers, and the subject of limited testing against a group of learners in class X SMA Negeri 1 Airpura.Validity test results lesson plan with a value of 92.06% and worksheets learners with a value of 88.91%, both at very valid criteria. The average value of the practicalities of the teacher's lesson plans amounted to 92.81% and 91.89% for worksheets learners, both with very practical criteria. While the average value of the practicalities of the learners of 74.54% with a practical criterion. These results indicate that, the learning device produced in the category unfit for teaching high school physics in terms of validity and practicalities